2007
DOI: 10.1007/s11270-007-9471-4
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum Dissolution Rate in Simulant Lung Fluid

Abstract: The aim of this study is to determine the solubility rate of tantalum contained in pyrochlore, columbite-tantalite and columbite in simulant lung fluid. The International Commission on Radiological Protection (ICRP), in its recommendation for limiting intakes of radionuclide by workers, has consistently recognized that the biological behavior of any specific material after incorporation can significantly diverge from model prevision. Model parameters should be adjusted to adapt the model for each specific subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Here we have focused on galena (PbS) as it is the primary form of lead associated with mining waste. 31 Mining represents an important study area with fine particles identified in processing plants, 32,33 chat piles, 30 and haul road dust; 34 aerosols in close proximity to a Pb smelter (Z ˇerjav, Slovenia) have shown to contain a median particle size distribution of 0.41 mm (unpublished results). PbS is known to be extremely insoluble with a solubility constant (K sp ) of 3.4 Â 10 À28 , a feature emphasized by its approximate 5% bioaccessibility within the gastrointestinal tract (GI tract) defined by both in vitro 35,36 and in vivo 37 experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Here we have focused on galena (PbS) as it is the primary form of lead associated with mining waste. 31 Mining represents an important study area with fine particles identified in processing plants, 32,33 chat piles, 30 and haul road dust; 34 aerosols in close proximity to a Pb smelter (Z ˇerjav, Slovenia) have shown to contain a median particle size distribution of 0.41 mm (unpublished results). PbS is known to be extremely insoluble with a solubility constant (K sp ) of 3.4 Â 10 À28 , a feature emphasized by its approximate 5% bioaccessibility within the gastrointestinal tract (GI tract) defined by both in vitro 35,36 and in vivo 37 experiments.…”
Section: Introductionmentioning
confidence: 99%